Earnings Management and Tax Aggressivity before and During the Covid-19 Pandemic (an Evidence from Indonesia) - Dianila Oktyawati; Hilda Octavana Siregar; Rumiyati Rumiyati (Ilomata International Journal of Tax and Accounting, 2023)
Companies facing financial crises tend to manipulate reported earnings in unfavorable markets. Earnings management is an effort to manage earnings by managers to meet the expected profit level to obtain personal gain. The Covid-19 pandemic has caused the government to issue various tax incentives that individuals and companies can utilize. Under these conditions, management as an internal party can manage earnings to meet its expectations. This study examines differences in earnings management before and during the Covid-19 pandemic and the effect of earnings management on tax aggressiveness. The data from this study are the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The sampling method is purposive sampling. The analytical method used is the comparative test and multiple regression analysis. The results of this study are the same in the level of tax avoidance, accrual earnings management, and actual management before and during the Covid-19 pandemic. This study also concludes that real earnings management negatively affects tax aggressiveness, while accrual earnings management does not. This research indicates that the government needs to increase supervision and control over the possible tax avoidance that companies can carry out. While accrual earnings management does not. This research indicates that the government needs to increase supervision and control over the possible tax avoidance that companies can carry out. While accrual earnings management does not. This research indicates that the government needs to increase supervision and control over the possible tax avoidance that companies can carry out.